2021
DOI: 10.1017/age.2021.3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sources of low cocoa production in Ghana: new insights from meta-analysis of old survey data

Abstract: Several studies have tried to estimate the productivity and input use efficiency of cocoa farmers in Ghana, but they shed limited light on their chronic nature and other sources of low production. This study extends the literature by analyzing a unique nationally representative sample that constitutes 30 years of production. The results showed that pure farmer technical inefficiency is not only 8 percent points larger than the regional technology gap, but also consistently dominated the overall performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Further, in addition to being highly prone to erosion, the soils of the Sudan and Guinea Savanna zones are characterized by low organic matter content (Oppong-Anane 2006). These distinctions in agro-ecological conditions do considerably contribute to differences in the production technology adopted by farm households in each zone and thus, the productivity difference, which is reflected by the disparities in the level of output generated across these zones and regions (Asante et al 2019;Asravor et al 2019;Danso-Abbeam and Baiyegunhi 2019;Owusu, 2016;Tsiboe 2021;Tsiboe, Aseete, and Djokoto 2021;Tsiboe, Asravor, and Osei 2019).…”
Section: Study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in addition to being highly prone to erosion, the soils of the Sudan and Guinea Savanna zones are characterized by low organic matter content (Oppong-Anane 2006). These distinctions in agro-ecological conditions do considerably contribute to differences in the production technology adopted by farm households in each zone and thus, the productivity difference, which is reflected by the disparities in the level of output generated across these zones and regions (Asante et al 2019;Asravor et al 2019;Danso-Abbeam and Baiyegunhi 2019;Owusu, 2016;Tsiboe 2021;Tsiboe, Aseete, and Djokoto 2021;Tsiboe, Asravor, and Osei 2019).…”
Section: Study Contextmentioning
confidence: 99%
“…Analogous to earlier studies which focus on vegetables (Tsiboe, Asravor, and Osei 2019), cocoa (Tsiboe 2021), and legumes (Tsiboe, Aseete, and Djokoto 2021), this study utilizes a nationally representative data set of 26,449 cereal farms, collated from 10 crosssectional population-based surveys periodically fielded throughout Ghana from 1987 to 2017. This novel data set represents three decades of cereal production experience at the farm level and has the widest coverage across time and space than that of previous cereal productivity studies conducted in Ghana.…”
Section: Study Contextmentioning
confidence: 99%
“…About 2 million cocoa producers have been estimated to be in West Africa and about 25% of them are females who own cocoa farms ( Barrientos, 2013 ). Due to the huge stake cocoa production has, researchers, international organizations and cocoa producing economies have come to agree that the future for sustainable cocoa production is bleak if the current average age of farmers is maintained, which is estimated to be above 50 years ( Laven and Boomsma, 2012 ; Oppong, 2015 ; Wessel and Quist-Wessel, 2015 ; Löwe, 2017 ; Akrofi-Atitianti et al., 2018 ; Tsiboe, 2021 ; Oyekale, 2021 ). To make matters worse, it has been found that the youth in the cocoa growing area are not interested in cocoa production as a business ( Bymolt et al., 2018 ).…”
Section: Why Cocoa Growing Communitiesmentioning
confidence: 99%
“…Several studies relevant to Ghanaian agriculture have investigated the primary drivers of resource use efficiency for rice [7][8][9][10][11][12], maize [12][13][14][15], legumes [16][17][18], cocoa [19][20][21][22], and vegetables [23], but with little attention on production shortfalls. An important category of crops that has received less attention despite the important role they play in the food security of households is the starchy staples.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the starchy staples have received little attention, against the backdrop of the critical roles these crops play, and the significant yield gaps observed in practice. Except for a few studies [12,22,23,25,27], all efficiency studies in Ghana used data based on a single season, and data size is limited to a few villages or at best a region. This data limitation and lack of locational heterogeneity masks important lessons that could emerge from analyzing a more comprehensive and heterogeneous sample.…”
Section: Introductionmentioning
confidence: 99%